Analisis Penerapan Pernyataan Standar Akuntansi Pemerintahan (PSAP) No. 01 Tentang Laporan Keuangan Desa (Studi pada Desa Awolagading Kecamatan Awangpone Kabupaten Bone) - Haryulan Saputri; Ida Farida (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This study aims to analyze the application of Government Accounting Standards Statement (PSAP) No. 01 in the preparation of financial statements in Awolagading Village, Awangpone Subdistrict, Bone Regency. The main focus of this research is to evaluate the conformity of village financial reports with the provisions of PSAP No. 01 and identify the challenges faced by the village in the preparation process. The method used was qualitative research with data collection techniques in the form of interviews and documentation. The results showed that Awolagading Village only prepared one of the seven components of the financial report required by PSAP No. 01, namely the Budget Realization Report (LRA). The main obstacles are the limited human resources who are competent in the field of government accounting, the lack of technical training, and the non-optimal use of the village financial system based on the Siskeudes application. Therefore, it is necessary to increase the capacity of village officials through training, technical assistance, and strengthening of financial management systems in order to meet applicable government accounting standards, so that transparency and accountability of village financial management can be better realized.